Anti-Angiogenic Activity of a Small Molecule STAT3 Inhibitor LLL12 - Bid, Hemant K.; Oswald, Duane; Li, Chenglong; London, Cheryl A.; Lin, Jiayuh; Houghton, Peter J. (PLOS ONE, 2012)
Background Recent data indicate the Signal Transducer and Activator of Transcription 3 (STAT3) pathway is required for VEGF production and angiogenesis in various types of cancers. STAT3 inhibitors have been shown to reduce tumor microvessel density in tumors but a direct anti-angiogenic activity has not been described. Methodology/Principal Findings We investigated the direct action of a small molecule inhibitor of STAT3 (LLL12) in human umbilical cord vascular endothelial cells (HUVECs) in vitro, in a Matrigel model for angiogenesis in vivo, and its antitumor activity in a xenograft model of osteosarcoma. LLL12 (100 nM) significantly inhibited VEGF-stimulated STAT3 phosphorylation in HUVECs, reduced their proliferation/migration and inhibited VEGF-induced tube formation. Morphologic analysis of LLL12 treated HUVECs demonstrated marked changes in actin/tubulin distribution and bundling. In scid mice, LLL12 reduced microvessel invasion into VEGF-infused Matrigel plugs by ∼90% at a dose of 5 mg/kg daily. Following a period of tumor progression (2 weeks), LLL12 completely suppressed further growth of established OS-1 osteosarcoma xenografts. Pharmacodynamic studies showed robust phosphorylated STAT3 in control tumors, whereas phospho-STAT3 was not detected in LLL12-treated OS-1 tumors. Treated tumors demonstrated decreased proliferation (Ki67 staining), and decreased microvessel density (CD34 staining), but no significant increase in apoptosis (TUNEL staining), relative to controls. Assay of angiogenic factors, using an antibody array, showed VEGF, MMP-9, Angiopoietin1/2, Tissue Factor and FGF-1 expression were dramatically reduced in LLL12-treated tumors compared to control tumors. Conclusions These findings provide the first evidence that LLL12 effectively inhibits tumor angiogenesis both in vitro and in vivo.